SADARI Counseling to Improve Public Awareness of Early Breast Cancer Detection - Pipih Salanti; Anggarani Prihantiningsih; Marisa Marcelina Limbong (ADI Publisher, 2026)
Breast cancer is one of the non-communicable diseases with a fairly high incidence rate among women in Indonesia. The low level of public awareness regarding the importance of early detection of breast cancer is one of the factors causing delays in treatment and increasing the risk of complications. One of the early detection efforts that can be carried out independently is SADARI (Periksa Payudara Sendiri). This community service activity aimed to improve public knowledge and awareness regarding the importance of breast self-examination (SADARI) as an initial step in breast cancer prevention. The activity was conducted from 9 to 27 March 2026 in RT 12 RW 01, Kelurahan Jagakarsa, South Jakarta. The implementation methods included preliminary surveys to 135 respondents, health education counseling, interactive discussions, demonstrations on how to perform SADARI correctly, and evaluations of participant understanding. The media used were posters and PowerPoint presentations. The results of the activity showed that the community had high enthusiasm during the counseling sessions. Participants were able to understand the definition of SADARI, its benefits, the signs and symptoms of breast abnormalities, and the correct steps for performing breast self-examination. The health counseling conducted directly was able to increase public knowledge regarding the importance of early detection of breast cancer. Through this activity, it is expected that the community will routinely practice SADARI as an effort to maintain breast health and prevent delays in breast cancer treatment.